2019
DOI: 10.1002/ecs2.2776
|View full text |Cite
|
Sign up to set email alerts
|

Negative impacts of summer heat on Sierra Nevada tree seedlings

Abstract: Understanding the response of forests to climate change is important for predicting changes in biodiversity and ecosystem services, including carbon storage. Seedlings represent a key demographic stage in these responses, because seedling establishment is necessary for population persistence and spread, and because the conditions allowing seedlings to survive and grow are often more restrictive than those adults can tolerate. However, detailed long-term data on the responses of individual seedlings to climatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 73 publications
0
12
0
Order By: Relevance
“…For pines, which are less sensitive to warming and drying than other species (Moran et al. ), shrub effects under a novel fire regime may be more important drivers of decreasing regeneration in our study area than changes in climate, though more research is needed on climate and shrub effects on regenerating pines.…”
Section: Discussionmentioning
confidence: 91%
“…For pines, which are less sensitive to warming and drying than other species (Moran et al. ), shrub effects under a novel fire regime may be more important drivers of decreasing regeneration in our study area than changes in climate, though more research is needed on climate and shrub effects on regenerating pines.…”
Section: Discussionmentioning
confidence: 91%
“…Growth of all age classes and seedling recruitment are affected by climate too. Our recent analysis found that hotter summer temperatures reduced the survival and growth of most species of Sierra Nevada tree seedlings (Moran et al 2019). Shifts in forest composition have already been observed.…”
Section: Introductionmentioning
confidence: 93%
“…For adult growth, the two best climate predictors were January minimum temperature and precipitation (Aubry-Kientz and Moran 2017) and for adult mortality July maximum temperature and precipitation (Appendix 2). For the survival of seedlings >10 cm in height, the best-fit model included July maximum temperature and total precipitation anomalies averaged over the current and past year, while for growth the current year July maximum temperature and total snow performed better (Moran et al 2019). However, projections for snow are highly uncertain because they combine already uncertain precipitation projections with calculations of how much falls as snow and the melt rate.…”
Section: Choice Of Climate Variablesmentioning
confidence: 99%
See 2 more Smart Citations